O procesie różnicowania: Tożsamość europejska w opozycji do Inności (Politeja, 2020)
On the Process of Othering. European Identity in Opposition to OthernessThe process of othering is the process of assigning a group or individual the role of the Other and creating one’s own identity in opposition to it. It deprives Others of the characteristics of “the same”: reason, dignity, love, pride, heroism, nobility, and ultimately human rights, regardless of whether the Other is a racial or religious group, a sexual minority or a nation. The process of othering can take a form of exploitation, oppression and even genocide because, as Richard Rorty put it, everything changes who is a fellow member of our moral community. Stanisław Konopacki describes it in relation to the question of European identity, built in opposition to Otherness. This opposition turns out to be extremely inspiring for an analysis of contemporary crises in the European Union. The paper presents a theoretical analysis of the process itself, its anthropological sources, and its consequences for the Habermas project of the contemporary European public sphere.